Study on a hydrophobic Ti-doped hydroxyapatite coating for corrosion protection of a titanium based alloy; RSC Advances; Vol. 6, iss. 90 - Surmeneva M. A. Maria Alexandrovna; Vladesku A. Alina; Surmenev R. A. Roman Anatolievich; Pantilimon C. M.; Braic M.; Kotrut M. K. Mikhay Kosmin (2016, 2016)
Title screen